ANALYSIS ON VIBRATION MODAL OF U-BIMETALLIC FINNED TUBES - MA TengFei; GUO JianYing; SHA FengHuan (Jixie qiangdu)
U-bimetallic finned tube is a new widely used heat exchange component.In order to predict and control the flowinduced vibration damage of U-bimetallic finned heat exchange tubes,their natural frequencies must be calculated accurately.Inplane and out-of-plane vibration modal of U-bimetallic finned tubes were investigated by means of the hammering method and finite element method.The influence of arc bending radius R of U-bimetallic finned tubes on their natural frequencies was analyzed.The finite element simulation results of natural frequencies of U-bimetallic finned tubes were compared with the measured values for free-free boundary condition,the maximum error of the first 18 order frequencies is 7.3%.The natural frequencies of U-bimetallic finned tubes decrease with increasing the arc radius R for clamped-hinged case.